2003
DOI: 10.1002/ppul.10290
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of specific yolk antibodies (IgY) may prevent Pseudomonas aeruginosa infections in patients with cystic fibrosis: A phase I feasibility study

Abstract: Respiratory infection is the major cause of morbidity and mortality in cystic fibrosis (CF) patients. Chronic Pseudomonas aeruginosa (PA) infections ultimately occur in virtually all patients. It is impossible to eradicate PA when a patient has been chronically colonized. Immunotherapy with specific egg-yolk antibodies (IgY) may be an alternative to antibiotics for the prevention of PA infections. We wanted to determine if treatment with specific IgY can prolong the period between the first and the second PA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 35 publications
(48 reference statements)
1
76
0
3
Order By: Relevance
“…Furthermore, in the event that entirely new viral strains appear, IgY can be produced within 6 weeks of vaccinating the hens. Finally, egg IgY is well tolerated in humans and has been used for long-term treatments of oral and intestinal pathogens without any serious side effects (5,6). Thus, this approach has great potential in helping to control highly pathogenic influenza viruses at the source of infection before they spread worldwide and cause a pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the event that entirely new viral strains appear, IgY can be produced within 6 weeks of vaccinating the hens. Finally, egg IgY is well tolerated in humans and has been used for long-term treatments of oral and intestinal pathogens without any serious side effects (5,6). Thus, this approach has great potential in helping to control highly pathogenic influenza viruses at the source of infection before they spread worldwide and cause a pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, results have shown that in patients suffering from cystic fibrosis (CF), IgY raised against Pseudomonas aeruginosa (a major cause of chronic lung infection in CF patients) can provide significant protection against colonization of the respiratory tract by this pathogenic organism (6). In addition, this treatment has been shown to be safe in humans, probably due to the fact that there are no Fc receptors for chicken IgY and there are no antibodies produced against IgY in people that are treated (1).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-Pseudomonas aeruginosa IgY antibodies employed in these experiments were harvested from egg yolks of White leghorn chickens immunized with 6 different Pseudomonas aeruginosa O-antigen strains (O1, O3, O5, O6, O9, and O11) and manufactured according to the standard procedure described by Kollberg et al 46 producing doses of 70 ml volume containing 50 mg IgY. Control IgY (C-IgY) (Immunsystem I.M.S. AB, Uppsala, Sweden) originates from naive (non-immunized) chickens and serves as chicken IgY polyclonal isotype control and specifically tested not to cross react with P. aeruginosa.…”
Section: Anti-pseudomonas Aeruginosa Igymentioning
confidence: 99%
“…In vitro IgY inhibits the adhesion of Salmonella enteritidis to human intestinal cells [10]. Oral administration of IgY from hens immunized with three serotypes of rotavirus prevents diarrhoea in mice infected with murine rotavirus Lung infections: Anti-pseudomonas IgY prevents colonization of Pseudomonas aeruginosa in the lungs and reduces the number of antibiotic treatment in patients with CF [11]. A phase III study supported by EU has just been concluded.…”
Section: Effectivitymentioning
confidence: 99%